LOCATION-ALLOCATION PROBLEMS IN THE PERSPECTIVE OF SUPPLY CHAIN: APPROACHES AND APPLICATIONS - Masudin, Ilyas (Jurnal Teknik Industri, 2019)
This article attempts to explore approaches and applications of the location-allocation problems in the supply chain perspective. A review has been done for articles which have relation with the approach of location-allocation problems that includes the drivers of the supply chain such as inventory, transportation, service level, and customer demand. Moreover, the application of location-allocation problems that consider supply chain drivers is also discussed. In this article, a discussion of location-allocation discussions previously investigated by researchers is done through a literature review published in several reputable journal databases. 57 journal articles successfully collected and reviewed related approaches and applications used by researchers in location-allocation problems in a supply chain perspective. Analysis of the findings of this article can be summarized that approaches of the location-allocation problem in supply chain perspective can be divided into 2 areas: the echelon of the supply chain and the drivers of the supply chain.